Inflation and the Skewness of the Distribution of Relative Price Changes: Empirical Evidence for Germany - Jörg Döpke; Christian Pierdzioch (Kiel Institute of World Economics (IfW), 2001)
The present paper uses German annual data covering the period 1969-2000 to present evidence on the link between aggregate inflation and the higher-order moments of the distribution of relative price changes. Our empirical findings confirm predictions of contributions to the theoretical literature suggesting that skewness of this distribution is an important explanatory variable for the inflation rate. Further, the skewness measure also helps to explain shifts in the Phillips curve. Moreover, a structural vector autoregression reveals that the skewness measure helps to explain the variations of real output and might, therefore, serve as a measure of supply side shocks hitting the economy.
Keywords: E31; 330; inflation; relative prices; distribution of relative prices changes; Inflationsrate; Relativer Preis; Inflation; Statistische Verteilung; Schätzung; Phillips-Kurve; Konjunktur; Gesamtwirtschaftliches Angebot; Schock; Deutschland